The Role Of Eating Attitude On Obesity-Related Eating Behavior In Overweight And Obese Women Of Urmia In 2012 - Maryam Mataji Amirrood; Mohammad Hosein Taghdisi; Mahmood Reza Gohari; Farzad Shidfar (Tehran University of Medical Sciences, 2015)
Background and Aim: Identifying obesity-related eating behavior predictors especially in women, who have a key role in their family's food basket, has a great importance in the prevention of obesity. The purpose of the present study is to determine the role of eating attitude on obesity-related eating behavior in overweight and obese women in Urmia. Materials and Methods: The present descriptive-analytical study was performed on 100 overweight or obese women covered by Shahid Nikkhah and No. 13 Health Centers in Urmia. Sampling was conducted through c onvenience method and women with a BMI equal to or more than 25 (kg/m2) were selected. Following their informed consent, they completed the questionnaires about demographic characteristics , attitude, and food behavior checklist. Data analysis was conducted using SPSS software version 18 and descriptive and inferential statistics (Chi-square , analysis of variance and regression ) at 0.05 significance level . Results: The result confirmed that there was a significant relationship between attitude and poor , average and good eating behavior groups of women (p=0.003).   Regression analysis revealed a positive and significant relationship between eating behavior and attitude scores (p=0.004, r=0.285) . Also, prediction of observed distribution in eating behavior was confirmed by age , anthropometric indices and demographic factors in addition to eating attitude . Conclusion: The study results confirmed the predictive role of eating attitude on obesity-related eating behavior. Therefore, it is recommended that correction of eating attitude be emphasized in the promotion of healthy eating behavior.